2017
DOI: 10.5004/dwt.2017.21333
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and theoretical evaluation of a hybrid solar still integrated with an air compressor using ANN

Abstract: a b s t r a c tAn experimental study has been performed to evaluate the single slope hybrid solar still integrated with heat pump (SSDHP). The purpose of this study is to determine the effectiveness of solar still and its modeling using artificial neural networks (ANNs) with the help of experimental data. Most influencing parameters (the solar radiation, glass cover temperature, basin temperature, water temperature and temperature of the evaporator) at an hour interval on the performance of hybrid solar still … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Hidouri et al [70] had determined performance of single slop hybrid solar still integrated with heat pump (SSDHP) by experimental study and compared with suitable ANN model. Authors evaluated the effect of an air compressor on productivity of SSDHP and predicted ANN models for different combination of most influential parameters (the solar radiation, glass cover temperature, basin temperature, water temperature and temperature of the evaporator).…”
Section: Ann Model For Performance Prediction Of Solar Stills (Ss)mentioning
confidence: 99%
“…Hidouri et al [70] had determined performance of single slop hybrid solar still integrated with heat pump (SSDHP) by experimental study and compared with suitable ANN model. Authors evaluated the effect of an air compressor on productivity of SSDHP and predicted ANN models for different combination of most influential parameters (the solar radiation, glass cover temperature, basin temperature, water temperature and temperature of the evaporator).…”
Section: Ann Model For Performance Prediction Of Solar Stills (Ss)mentioning
confidence: 99%
“…Effect on distillate yield by covering nearby ground of sand bed solar still with polythene sheet and coal powder have been reported by Tiwari and Mishra [21]. Using ANN model a hybrid solar distiller unit integrated with an air compressor has been reported by Hidouri et al [22]. Rabhi et al [23] have reported the augmentation of fins (in basin area) and external condenser with the solar still.…”
Section: Introductionmentioning
confidence: 95%
“…The effect of different salt concentrations on the performance of the solar still has been reported by Dumka et al [12]. Experimental evaluation of hybrid solar still integrated with the air compressor has been reported by Hidouri et al [13]. Exergo-enviro-economic performance evaluation of a single slope distiller unit has been reported by Joshi and Tiwari [14].…”
Section: Introductionmentioning
confidence: 99%